Early Nasal Intermittent Positive Pressure Ventilation (NIPPV) versus Nasal Continuous Positive Airway Pressure (NCPAP) for Respiratory Distress Syndrome (RDS) in Infants of 28-36 weeks gestational age: a Randomized Controlled Trial - Tisha Ann Skariah; Leslie Edward Lewis (Mashhad University of Medical Sciences, 2019)
Background: Early nasal continuous positive airway pressure (NCPAP) has emerged as a primary modality of respiratory support for preterm infants withrespiratory distress syndrome (RDS). However, 30%-40% of these newborns need subsequent mechanical ventilation. Nasal intermittent positive pressure ventilation (NIPPV) is a promising alternative to NCPAP, especially in post-extubation settings, apnea of prematurity, or NCPAP failure as the primary mode of respiratory support in RDS. Application of these two methods in neonates with RDS needs further studies.  Methods: This open-label randomized clinical trial (RCT) was stratified by gestational age (i.e., 28-32 and 33-36 weeks). The sample included 78 infants divided into the two groups of 37 NIPPV and 41 CPAP.  We compared the effect of ventilator delivered asynchronous NIPPV with NCPAP in reducing the need for invasive ventilation within 48 h of non-invasive support in infants of 28-36 weeks with RDS [onset of distress within ≤ 6 h of life with a fraction of inspired oxygen (FiO2) ≥ 0.25 compatible with chest radiograph]. The FiO2 > 0.3 and/or Downes score ≥ 4 were the indications for surfactant therapy administered by endotracheal tube. The infants were extubated and returned to their initial assigned mode of support within 60 min.  The primary outcome was considered as failure of the allocated mode within 48 h. Results: According to our findings, the two groups showed no significant difference in terms of failure rates with 5 (13.5%) and 6 (15%) failed NIPPV and NCPAP cases (P=0.8). There was a trend toward less surfactant therapy in NIPPV [12 (32.4%) vs. 22 (53.7%), P=0.06], and lower Downes score in the first 12 h. The hazard ratio (HR; adjusted for gestation, surfactant therapy, and birth weight) for failure in NIPPV was similar to that of NCPAP (HR=1.03) at 95% confidence interval. No difference in air leaks or abdominal distension was noted between the two groups. Conclusion: Early NIPPV may not have a benefit, compared to NCPAP as a primary mode of respiratory support for infants with RDS.